2021
DOI: 10.1021/acsami.1c17807
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Configuration of Copper Oxide–Ceria Catalysts in NO Reduction with CO: Superior Performance of a Copper–Ceria Solid Solution

Abstract: Various copper−ceria-based composites have attracted attention as efficient catalysts for the reduction of NO with CO. In this comparative study, we have examined the catalytic potential of different configurations of copper oxide−ceria catalysts, including catalysts based on a copper−ceria solid solution, copper oxide particles supported on ceria, and ball-milled copper oxide−ceria. The structurally different interfaces between the constituents of these catalysts afforded very different catalytic performances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 59 publications
0
30
0
Order By: Relevance
“…Due to their unusual physicochemical characteristics [ 63 ], in a variety of catalytic reactions, including the production of DMC by MeOH-oxidative carbonation [ 64 ], carbonate materials that support Cu nanoparticles have drawn a lot of attention in recent years [ 65 , 66 , 67 , 68 , 69 ]. It is well-known that the distribution of active metal species and particle size significantly affect catalytic effectiveness [ 70 ].…”
Section: Developed Methods For Green Dmc Synthesismentioning
confidence: 99%
“…Due to their unusual physicochemical characteristics [ 63 ], in a variety of catalytic reactions, including the production of DMC by MeOH-oxidative carbonation [ 64 ], carbonate materials that support Cu nanoparticles have drawn a lot of attention in recent years [ 65 , 66 , 67 , 68 , 69 ]. It is well-known that the distribution of active metal species and particle size significantly affect catalytic effectiveness [ 70 ].…”
Section: Developed Methods For Green Dmc Synthesismentioning
confidence: 99%
“…After three reaction cycles, no loss of catalytic activity and selectivity for Au 38 S 2 (SAdm) 20 was observed. The high efficiency of the 1 O 2 generation with Au 38 S 2 (SAdm) 20 prompted the further investigation of the photocatalytic activity of the Au 38 S 2 (SAdm) 20 nanoclusters used in a one-step selective chemical transformation of benzylamine to N-(phenylmethylene)benzenemethanamine under an LED light (λ ≈ 455 nm) in the atmosphere of O 2 . In the same reactions, a 99% conversion of the substrate was reached in 0.5 h with >99% selectivity; this result is much better than supported Au nanoparticles (6-12 nm) [61].…”
Section: Sulfide To Sulfoxidementioning
confidence: 99%
“…TiO 2 -based semiconductors have been well documented in photo-oxidations [15][16][17]. Recently, supported small-sized CuO x NPs (3-5 nm), with a high population of surface oxygen vacancies, have been applied in a serial of redox reactions [18][19][20][21]. Firstly, these CuO NPs can aid the minimizing recombination of photo-generated electrons/holes, thus improving the photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Ceria doped with various metals, including Cu, Co, Ni, and Fe, has been shown to offer significant potential for CO oxidation and NO reduction [23] . In a previous comparative study of different configurations of copper‐ceria catalysts, we showed that a solid solution with copper incorporated into the ceria lattice exhibits superior catalytic performance in the NO reduction with CO compared to corresponding catalysts made up of copper oxide particles supported on ceria and ball‐milled mechanical mixtures of these components [24] . Recently, Rood et al.…”
Section: Introductionmentioning
confidence: 98%
“…[23] In a previous comparative study of different configurations of copper-ceria catalysts, we showed that a solid solution with copper incorporated into the ceria lattice exhibits superior catalytic performance in the NO reduction with CO compared to corresponding catalysts made up of copper oxide particles supported on ceria and ball-milled mechanical mixtures of these components. [24] Recently, Rood et al demonstrated that copper and chromium doping into the crystal lattice of ceria nanorods exposing the (111) facets increases the concentration of oxygen defects and the surface and bulk reducibility leading to enhanced N 2 -selectivity in the reduction of NO with CO. [25] These findings prompted us to prepare multicomponent CuCrCeO x , CuCeO x , and CrCeO x solid solution catalysts to study the synergy of Cu and Cr co-doping in the NO reduction with CO in the presence as well as absence of oxygen and to evaluate the influence of water and SO 2 on the catalyst stability.…”
Section: Introductionmentioning
confidence: 99%